Science Education Research and Practices in Taiwan 2015
DOI: 10.1007/978-981-287-472-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Public Communication of Science and Technology in Taiwan

Abstract: Data collection and labeling are critical bottlenecks in the deployment of machine learning applications. With the increasing complexity and diversity of applications, the need for efficient and scalable data collection and labeling techniques has become paramount. This paper provides a review of the state-of-the-art methods in data collection, data labeling, and the improvement of existing data and models. By integrating perspectives from both the machine learning and data management communities, we aim to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Finally, Wang and Yang (2016) also reviewed the existing articles published by scholars in Taiwan and suggested three key elements for the implementation of all emerging learning technology in education: nature of ICT, mediation model, and transforming model to understand how to make learning technology pedagogically and practically effective in improving teaching effectiveness and student learning effectiveness (p. xx). Taking a different angle to investigate the impact of media and e-learning, Huang (2016) commented that the difficulties and challenges of science communication are primarily coming from the transformation between "public communication of science" and "communicating science to the public." So, he proposed three steps, namely to be correct, to be popular, and to be reflective, to advance our understanding of the power of science media in science education.…”
Section: Innovative Technology For Science Learning and Instruction Imentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, Wang and Yang (2016) also reviewed the existing articles published by scholars in Taiwan and suggested three key elements for the implementation of all emerging learning technology in education: nature of ICT, mediation model, and transforming model to understand how to make learning technology pedagogically and practically effective in improving teaching effectiveness and student learning effectiveness (p. xx). Taking a different angle to investigate the impact of media and e-learning, Huang (2016) commented that the difficulties and challenges of science communication are primarily coming from the transformation between "public communication of science" and "communicating science to the public." So, he proposed three steps, namely to be correct, to be popular, and to be reflective, to advance our understanding of the power of science media in science education.…”
Section: Innovative Technology For Science Learning and Instruction Imentioning
confidence: 98%
“…In another area of neuroscience, Liu and Huang (2016) advocated that neuroscience can be a link to bridge the gaps among research trends, methodologies, and applications among different disciplines. Huang andLiu (2012, 2013) analyzed students' performance on mental rotation of chemical compounds via the use of ERPs with university students. They found that both high-and low-achieving students used similar strategies of mental rotation in identifying 3D chemical structural formulae and even found chemical element symbols to be meaningless for low-achieving students.…”
Section: Innovative Technology For Science Learning and Instruction Imentioning
confidence: 99%
“…Members of Taiwan STS Association cover professions including historians, sociologists, philosophers, educators, scientists and engineers. While this association shares something in common with the Association of Science Education in Taiwan, due to the similar disciplinary make-up of their members, it has a different emphasis: more on the interdisciplinary perspectives of the overall social sciences and humanities, and more on research and promotion of policymaking and practical strategies for public participation in science (Huang, 2016). In 2007, MOST launched 'Development of Taiwan Science Communication Industry', which promotes science communication by integrating scholars, experts and media companies through a funding budget.…”
Section: From the Budding To Blooming Of Science Communication Academia And Practicementioning
confidence: 99%
“…Science and technology together are regarded as an 'imported culture' for any in-depth image of the Taiwanese, and many factors, such as national dignity and self-esteem, are involved in disseminating scientific knowledge (Huang, 2016). As a country, Taiwan is proud that in such a short period it has caught up with the developmental pace in the world with regards to infrastructure and institutionalisation of science communication.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Television stands out as the main source of science information for Americans, Europeans and Asians (e.g., American Academy of Arts and Sciences, 2018; Huang, 2016;Jamieson et al, 2017;National Science Board, 2019). The Internet is a close second for audiences seeking general science and technology information, and the primary source for those interested in specific science issues (AAAS, 2019;Jamieson et al, 2017;Pew, 2006).…”
Section: Free-choice Science Learning Researchmentioning
confidence: 99%